The Role of Father and Mother Attachment on The Career Decision-Making Style of Female Balinese High School Students - Laksmi Ananda Dewi; Susilawati, Luh Kadek Pande Ary (Jurnal Psikiatri Surabaya, 2026)
Introductions: Career decision-making in female Balinese high school students is influenced by parental attachment, particularly in a patriarchal cultural context. This study examines the role of attachment to fathers and mothers in predicting career decision-making styles (rational, intuitive, and dependent). Methods: A total of 125 female high school students in Denpasar, Bali, were selected through cluster sampling. Data collection utilized the Inventory of Parent and Peer Attachment (IPPA) and the Assessment of Career Decision Making (ACDM). Multiple linear regression analysis was conducted using JAMOVI and SPSS to determine the significance of parental attachment on decision-making styles. Results: The findings indicate that paternal attachment significantly influenced rational (p = 0.021), intuitive (p = 0.023), and dependent (p = 0.004) decision-making styles. Maternal attachment significantly influenced rational (p = 0.033) and intuitive (p = 0.019) styles but had no significant effect on dependent decision-making (p = 0.611). These results suggest that cultural norms emphasizing paternal authority may contribute to the greater influence of fathers on dependent decision-making. To foster independent career decision-making among girls, efforts should be made to encourage equal parental involvement, integrate career counseling programs, and challenge traditional gender norms in career planning. Conclusion: The study highlights the importance of parental attachment in shaping career decision-making. While both parents play a role, fathers have a greater impact on dependent decision-making, likely due to Balinese cultural values. Promoting balanced parental involvement and independent decision-making strategies can better support female students’ career choices.